Circuits through prescribed edges. Issue 4 (24th August 2019) - Knappe, Paul; Pitz, Max
Abstract: We prove that a connected graph G contains a circuit—a closed walk that repeats no edges—through any k prescribed edges if and only if G contains no odd cut of size at most k .